2013
DOI: 10.1155/2013/157247
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Ceramic Bearing Surfaces following Total Hip Replacement: A Systematic Review

Abstract: Ceramic bearing surfaces are increasingly used for total hip replacement, notwithstanding that concern is still related to ceramic brittleness and its possible mechanical failure. The aim of this systematic review is to answer three questions: (1) Are there risk factors for ceramic component fracture following total hip replacement? (2) Is it possible to perform an early diagnosis of ceramic component failure before catastrophic fracture occurs? (3) Is it possible to draw guidelines for revision surgery after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 68 publications
2
83
0
4
Order By: Relevance
“…In our opinion, this might have caused edge loading and/or stress concentration in the peripheral portion of the liner resulting from hyperflexion and wide abduction [17]. Likewise, Traina et al [26] in their review article of CoC THA, said that the accepted hypothesis as a causative factor for ceramic liner fracture is the cyclic impingement between the neck of the stem and the acetabular component.…”
Section: Discussionmentioning
confidence: 93%
“…In our opinion, this might have caused edge loading and/or stress concentration in the peripheral portion of the liner resulting from hyperflexion and wide abduction [17]. Likewise, Traina et al [26] in their review article of CoC THA, said that the accepted hypothesis as a causative factor for ceramic liner fracture is the cyclic impingement between the neck of the stem and the acetabular component.…”
Section: Discussionmentioning
confidence: 93%
“…Theoretical advantages of ceramic compared with metal heads are that the smooth finish, hardness, and wettability lead to less friction, more lubrication, and less scratching between the bearing surfaces and thus lower rates of liner wear and osteolysis [37], although this is based on use of historical UHMWPE (gamma air-sterilized polyethylene) and older manufacturing processes of femoral heads that may not generalize to contemporary implants. One of the major concerns about ceramic heads, especially in ceramic-on-ceramic articulation, is the risk of component fracture; however, this has shown to be decreased in ceramic-on-polyethylene bearing surfaces [1,39]. Results from the Australian registry suggest that ceramic heads have a slightly higher revision risk among patients with osteoarthritis over a 10-year period when used with HXLPE (gender/age-adjusted hazard ratio [HR], 1.03; 95% confidence interval, 0.94-1.13) [28].…”
Section: Introductionmentioning
confidence: 99%
“…CoC bearings have had mixed results throughout the literature, with early generations experiencing issues with ceramic fracture and squeaking [1]. The newest generation of ceramics exhibit an exceedingly low fracture risk [2,3], yet the squeaking hip continues to be an issue [4]. Ranawat et al reported 10.7 % of patients with CoC hips complained of audible squeaking [5].…”
Section: Bearing Options In Total Hip Arthroplastymentioning
confidence: 99%